2007
DOI: 10.1073/pnas.0610250104
|View full text |Cite
|
Sign up to set email alerts
|

Linkage proof for PTPN22 , a rheumatoid arthritis susceptibility gene and a human autoimmunity gene

Abstract: The tyrosine phosphatase PTPN22 allele 1858T has been associated with rheumatoid arthritis (RA) and other autoimmune diseases. RA is the most frequent of those multifactorial diseases. The RA association was usually restricted to serum rheumatoid factor positive disease (RF ؉ ). No interaction was shown with HLA-DRB1, the first RA gene. Many case-control studies replicated the RA association, showing an allele frequency increase of Ϸ5% on average and large variations of population allele frequencies (2.1-15.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 41 publications
3
49
0
2
Order By: Relevance
“…[5][6][7][9][10][11] These now include EOMG, 12,16 as confirmed here. PTPN22 is mainly expressed in lymphocytes, in which it physically associates with Csk kinase, an important suppressor of Src family kinases, which mediate TCR signaling.…”
Section: Ptpn22 Il-2 and Paraneoplastic Myasthenia Gravis W-y Chuangmentioning
confidence: 54%
See 1 more Smart Citation
“…[5][6][7][9][10][11] These now include EOMG, 12,16 as confirmed here. PTPN22 is mainly expressed in lymphocytes, in which it physically associates with Csk kinase, an important suppressor of Src family kinases, which mediate TCR signaling.…”
Section: Ptpn22 Il-2 and Paraneoplastic Myasthenia Gravis W-y Chuangmentioning
confidence: 54%
“…Their presumed low-expression or low-activity genotypes predispose to multiple autoimmune diseases, including type 1 diabetes, [5][6][7][8][9] Graves' disease, 7,8 hypothyroidism, 6,8 systemic lupus erythematosus, 6,10 rheumatoid arthritis, 6,11 and non-thymoma myasthenia gravis (MG). 12 However, the function of PTPN22 in this tolerance failure 13 has become debatable because of the paradoxically stronger inhibition of T-cell activation 14 by the autoimmunity-prone PTPN22 þ 1858T/T ( 620 W) or C/T genotype rather than the protective þ 1858C/C ( 620 R).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we found much stronger association of 1858T with RF-negative than with RF-positive RA, in contrast to some other studies. 8,17 However, many laboratories 6,7,18 did not observe substantial differences between 1858T frequencies in RF-positive and RF-negative RA patients, and Dieudé et al 5 found 1858T-RF association in transmission disequilibrium test, but not in affected sib-pair test. Therefore, the restriction of the association of 1858T with RF-positive RA is still controversial and requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that B‐cells from carriers of this PTPN22 risk allele contained high frequencies of autoreactive clones compared with those from non‐carriers showing how a single polymorphism at one genetic locus can affect the B‐cell repertoire 61. This PTPN22 polymorphism is a gain‐of‐function variant leading to reduced B‐ and T‐cell receptor signalling,62, 63 and has been associated with a range of autoimmune diseases, including RA,64, 65 type 1 diabetes66 and SLE 67. Similar studies on variation in other genes are likely to provide further useful information on how specific biological pathways regulate the B‐cell repertoire.…”
Section: Slementioning
confidence: 99%